Surgical Treatment of Wrist Arthritis in Young Patients. Issue 3 (March 2020) - Campbell, Collier C.; Neustein, Thomas M.; Daly, Charles A.; Wagner, Eric R.
Abstract : Surgical treatment of wrist arthritis in the younger patient population remains a challenging issue, and various surgical options need to be carefully considered for each patient. Proximal row carpectomy and 4-corner arthrodesis have proven to be reliable options for reducing pain and restoring adequate function in most young high-demand patients if the lunate facet is spared. Selective neurectomy has proven to be a promising stand-alone or complementary procedure for the treatment of pain that is associated with wrist arthritis in patients of all ages, with spared motion and the opportunity to perform additional procedures if pain continues. Alternative procedures, including capitolunate arthrodesis, total wrist arthrodesis, radial styloidectomy, total wrist arthroplasty, and wrist hemiarthroplasty, have considerable strengths and weaknesses and need to be studied further in younger patients.